Students' Critical Thinking Skills in Solving Mathematical Problems: Systematic Literature Review - I Putu Pasek Suryawan; I Gusti Putu Sudiarta; I Gusti Putu Suharta (Universitas Pendidikan Ganesha, 2023)
To develop mathematical critical thinking skills, students are expected to have a fighting attitude in solving mathematical problems. This can support learning that is oriented towards students' critical thinking skills. The purpose of this research is to analyze the trend of studying critical thinking skills in solving students' mathematical problems. This research uses the systematic literature review method which is carried out by identifying, assessing, and interpreting all available research evidence by studying indicators and how to bring up students' mathematical critical thinking skills as the object of research. The design used is to summarize, review, and analyze 25 articles that are very relevant to the object of research in Sinta accredited journals, indexed by Scopus and Web of Science. The results of this systematic literature review state that aspects of argumentation and reasoning are very important to be developed in solving mathematical problems. Implementing problem-based learning has positive effectiveness towards improving mathematical critical thinking skills and digitalization of learning is needed in facilitating students' critical thinking. Digitalization of learning can be developing problem-based digital modules that facilitate students' cognitive conflicts. The conclusion in this research are different indicators used to measure students' critical thinking skills, different aspects of interpreting indicators, the use of PBL, and the use of ICT.